Pembelajaran Rekayasa Perangkat Lunak dengan Metode Problem-Based Learning di Politeknik Negeri Batam - Nur Zahrati Janah (JURNAL INTEGRASI, 2014)
Software Engineering (SE) is one of the core courses in Informatics Engineering. Teaching SE faces many challenges because the objective of this course is that the students are able to create many artifacts along the software development process, not merely recalling information or theory that has been taught. It is often found that students cannot synchronize their work starting from the early phase of software development until the last stage of implementation. The unavailability of reference books that explain software engineering steps, including the implementation, accompanied by relevant case study that is easy to be understood by students is also a hindering factor. Therefore, this paper will propose a teaching method for SE course which implements problem -based learning. The proposed method includes material composition; problem, project, and team; sessions in the class; tools utilization; and assessment methods. This method considers the outcomes of SE course in the past, and its tight relation with other courses, such as Final Project I and Object Oriented Programming.